Strengthening Early Childhood English Pronunciation through Tiny Pronounce: A Speech Recognition–Based Learning Innovation - Astutik, Ari; Azizah, Anisa’ Nur; Sulistiyani, Sulistiyani (Journal of Community Service and Empowerment, 2026)
English pronunciation is a fundamental skill that should be developed from an early age, particularly in kindergarten (TK). However, many kindergarten teachers face challenges in teaching accurate pronunciation due to limited phonetic competence and the lack of interactive learning media. This Community Service Program (PKM) aimed to enhance the competence of RA Hidayatullah teachers in teaching English pronunciation through the utilization of Tiny Pronounce, a technology-based application equipped with speech recognition features. The implementation included socialization, training, practice, and simulation of the application, followed by evaluation using pre-test and post-test. The results revealed a 40% improvement in teachers’ competence, covering skills in pronouncing vowels, consonants, intonation, and stress, along with increases in motivation, self-confidence, and technology-based pedagogical skills. These findings demonstrate that the Tiny Pronounce application is effective in supporting kindergarten teachers to teach English pronunciation in a more interactive, engaging, and age-appropriate manner.